The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00402-003-0601-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative functional outcome and stability in recurrent traumatic anteroinferior glenohumeral instability: comparison of two different surgical capsular reconstruction techniques

Abstract: Our results demonstrate no significant differences between the two capsular reconstruction techniques regarding patient's satisfaction, Rowe and Constant Scores. However, the anatomically orientated anteroinferior capsular shift leads to a significantly smaller external rotation deficit and seems to offer a more reliable postoperative stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The results of this study indicate that open Bankart repair and capsular shift procedures could provide good results in the treatment of traumatic recurrent anterior instability of the shoulder. These findings support and extend previous studies examining the relationship between Bankart size and the postoperative functions [3, 5–8, 16, 17], in which severity of Bankart lesion, labrum pathology, and glenoid condition were correlated to the postoperative prognosis [10]. Moreover, our findings suggested that the size of the Bankart lesion was negatively associated with surgical outcomes (Table 4), while the age at first dislocation, age at operation, and duration of instability were not associated with the surgical outcomes (Table 5).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study indicate that open Bankart repair and capsular shift procedures could provide good results in the treatment of traumatic recurrent anterior instability of the shoulder. These findings support and extend previous studies examining the relationship between Bankart size and the postoperative functions [3, 5–8, 16, 17], in which severity of Bankart lesion, labrum pathology, and glenoid condition were correlated to the postoperative prognosis [10]. Moreover, our findings suggested that the size of the Bankart lesion was negatively associated with surgical outcomes (Table 4), while the age at first dislocation, age at operation, and duration of instability were not associated with the surgical outcomes (Table 5).…”
Section: Discussionsupporting
confidence: 90%
“…We used the method of glenoid‐based capsular shift described by Neer and Foster [18]. Preservation of shoulder external rotation is essential if there is the demand to return to the same level of play as before the surgery [5, 12, 19, 20]. The average loss of external rotation after operation was 10°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States (n = 10; 16.7%), 4 , 5 , 8 , 11 , 15 , 17 , 40 , 50 , 59 , 68 France (n = 5; 8.3%), 41 , 46 , 48 , 55 , 67 Germany (n = 5, 8.3%), 19 , 23 , 26 , 43 , 45 and Italy (n = 5; 8.3%) 13 , 21 , 42 , 54 , 60 were the most represented countries that published studies. Of the 60 included studies, there were 14 (n = 14; 12.8%) bony stabilization procedure groups and 95 (n = 95; 87.2%) soft-tissue procedure study groups.…”
Section: Resultsmentioning
confidence: 99%
“…Rowe [33] reported in 1978 excellent and good functional results in 97% and a recurrence rate of 3.5% with this technique after an average follow-up duration of 6 years. Different studies have proven this technique as a sucessful treatment for traumatic anterior shoulder instability with recurrence rates below 10% [13,15,16,24,29,32,40]. However, long-term follow-up studies and investigations including subluxation as a failure demonstrated a higher recurrence rate than expected [26].…”
Section: Introductionmentioning
confidence: 99%